Family Poverty and the Labor Market - Michael Förster (Luxembourg Income Study (LIS), 1994)
This paper studies the impact of employment, unemployment and non-activity on the relative income status of non-elderly families as well as different working patterns (full-time/part-time employment) among different family types.
Keywords: 330